A legal analysis of the social protection for workers engaged in atypical forms of employment in South Africa - Sekokotla, Mpho (My University, 2024)
The rapid growth in atypical employment across the globe brought both negative and positive impact to the labour market. For South Africa, in terms of curbing the evergrowing unemployment rate, it created problems for persons engaged in non-standard forms of employment as the labour legislation did not evolve when the labour market evolved. This failure to evolve included insufficient labour protection afforded to the atypical workers while stronger protection mechanisms were put in place for workers in standard employment. This study analyses the challenges that atypical employees are subjected to, and these can be seen through their lack of access to social protection which includes inter alia, access to benefits such as social security and employment incentives that are enjoyed by employees in permanent employment. A critique is made of the various mechanisms which the state has attempted to make in redressing the challenge followed by a comparative study between South Africa, the Netherlands, and the United Kingdom from which a few lessons can be drawn for South Africa to improve the working conditions of atypical workers. The study further draws on the existing international and regional labour standards coupled with the South African Constitution of 1996, as well as the national experience to make policy recommendations that will ensure the legal protection of these categories of workers. It is submitted that social justice and the democratisation of the workplace will remain a pipe dream if workers in non-standard employment continue to be excluded from the coverage of labour protection.
Thesis (Ph.D. (Laws)) --University of Limpopo, 2024
Keywords: Atypical employment; Labour protection; Social security; Job security; Income security; Decent work; Maternity protection; Maternity leave -- Law and legislation -- South Africa -- Limpopo.; Social security -- South Africa -- Limpopo.; Labour law -- South Africa -- Limpopo Province; Temporary employment -- Law and legislation -- South Africa; Labor contract